Analysis of the impact of emergency care on the incidence of in-hospital complications in patients with acute abdomen and the incidence of complications - Jin, Ruimian; Deng, Yuquan; Yang, Jing (Frontiers in Public Health, 2025)
ObjectiveTo investigate the effect of graded emergency nursing intervention on the incidence of in-hospital complications in patients with acute abdomen and to evaluate patient satisfaction with nursing care.MethodsBetween June 2021 and June 2023, 100 patients with acute abdomen (85 with acute appendicitis) were randomly assigned to a control group (routine nursing care, n = 50) or an emergency care (EC) group (graded emergency intervention, n = 50). Graded emergency nursing intervention was implemented based on the Emergency Severity Index (ESI) version 4, which stratifies patients from Level I (life-threatening) to Level V (non-urgent). The EC group received structured emergency triage by trained nursing teams, including systematic protocols for patient observation, inquiry, physical examination, and condition analysis. Outcomes included emergency care efficiency indicators (consultation time, examination time, emergency department stay, trauma control time, hospital stay), complication rates (e.g., abdominal infection, hemorrhage, puncture site infection, subcutaneous emphysema), clinical symptom recovery (abdominal pain duration, gastrointestinal recovery time), and nursing satisfaction scores. Data were analyzed using t-tests and chi-square tests via SPSS 21.0, with significance set at p < 0.05.ResultsThe EC group showed significantly lower rates of in-hospital complications (2% vs. 14%, p < 0.05), faster clinical response times (shorter consultation and examination times, reduced emergency department and hospital stay durations), and quicker symptom recovery compared to the control group (p < 0.05). Nursing satisfaction scores were also significantly higher in the EC group (p < 0.05).ConclusionGraded emergency nursing intervention—based on triage acuity, structured symptom assessment, and trained response teams—effectively reduces the incidence of complications, enhances emergency response efficiency, shortens recovery and hospital stay durations, and improves patient satisfaction. This approach is clinically valuable and recommended for broader implementation.